Influence of Efficient Use of Resources on Pupils Performance in Kenya Certificate of Primary Education in Public Primary Schools in Butula Sub -County, Kenya - Edabu, Paul; Onyango, Priscilla Atieno (IJRDO- Journal of Educational Research, 2018)
The purpose of this study was to investigate the influence of efficiency use of resources on KCPE performance in primary schools in Butula sub county, Kenya. The study was guided by system approach to education planning theory and the rationale of supervision theory. The study applied the methodology of mixed method approach that deals with both quantitative and qualitative data. The study adopted a concurrent triangulation research design. Data analysis was done using Microsoft excel and (SPSS version 23) statistical tool. Qualitative data was analyzed thematically along the study objectives. Quantitative data was analyzed using descriptive statistics (Frequency tables, means, and standard deviation) and inferential statistics (ANOVA). The study findings revealed that with efficient utilization of resourcesenhanced relationship between teachers and school inspectors, government controls are important in regulating and monitoring the performance of primary schools. The finding on null hypothesis using ANOVA test indicated that the independent variables significantly (Fo = 6.190>Fc= 5.324; α< 0.05; df = 10, 106; p = 0.005) explain the variance in KCPE performance in primary schools in Butula sub-county, Kenya. This inferred that efficiency use of resources made a notable difference in the KCPE pupils’ performance in primary schools in Butula Sub County in Kenya. The findings conclude that inspectors/supervisors should act as professionals in creating a conducive learning and teaching atmosphere for the teacher to conduct his/her professional expertise to the learners in school.  The study recommended that in-service educational growth enables conducive environment for concentration and promoting teachers’ professional ability to meet students’ needs in schools.